2021
DOI: 10.3390/ijms22020685
|View full text |Cite
|
Sign up to set email alerts
|

Stem Photosynthesis—A Key Element of Grass Pea (Lathyrus sativus L.) Acclimatisation to Salinity

Abstract: Grass pea (Lathyrus sativus) is a leguminous plant of outstanding tolerance to abiotic stress. The aim of the presented study was to describe the mechanism of grass pea (Lathyrus sativus L.) photosynthetic apparatus acclimatisation strategies to salinity stress. The seedlings were cultivated in a hydroponic system in media containing various concentrations of NaCl (0, 50, and 100 mM), imitating none, moderate, and severe salinity, respectively, for three weeks. In order to characterise the function and structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 149 publications
(141 reference statements)
1
15
0
1
Order By: Relevance
“…Abnormalities in the efficiency of OEC activity as well as in the size of the plastoquinone pool resulted in reduced efficiency of PSII (Y(II)) that led to permanent damage of the photosynthetic apparatus (Y(NO)). A similar effect was observed when the photosynthetic apparatus formation was disturbed in plants subjected to various abiotic stressors limiting the synthesis pathways of structural elements of the photosynthetic apparatus [33,43,48,53]. The application of B and RB LED resulted in no significant differences in the photosynthetic apparatus response, which indicated optimal conditions for its formation in gerbera.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Abnormalities in the efficiency of OEC activity as well as in the size of the plastoquinone pool resulted in reduced efficiency of PSII (Y(II)) that led to permanent damage of the photosynthetic apparatus (Y(NO)). A similar effect was observed when the photosynthetic apparatus formation was disturbed in plants subjected to various abiotic stressors limiting the synthesis pathways of structural elements of the photosynthetic apparatus [33,43,48,53]. The application of B and RB LED resulted in no significant differences in the photosynthetic apparatus response, which indicated optimal conditions for its formation in gerbera.…”
Section: Discussionsupporting
confidence: 54%
“…Both the visible and near-infrared spectra are crucial for the formation of a well-functioning photosynthetic apparatus [32]. The efficiency of photosynthesis depends on the sequence of metabolic processes during light and dark reactions, the activity of enzymes involved in carbon assimilation, the structure of the photosynthetic apparatus, and the transport of photosynthetic intermediates between cellular compartments [33]. The quality of light affects the photosynthesis, e.g., by its influence on the chloroplast structure, regulation of leaf size, opening of the stomata, or photosystem II (PS II) [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipids are the major components of membranes and have a crucial role in stress signalling in plants [ 37 ]. Studying lipid membrane compatibility and composition may show the physiological status of plant cells under stress conditions [ 38 ]. Our results showed that plant transformation did not affect the total lipid concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Фотосинтез як основний процес метаболізму в рослині забезпечує енергосубстратне форування врожаю, поєднане із процесами поглинання елементів мінерального живлення протягом вегетаційного періоду. Разом із тим засвоєння поживних речовин визначає інтенсивність перебігу всіх фізіолого-біохімічних процесів у рослинному організмі та залежить від них [11]. Провідну роль під час поглинання енергії фотосинтетично активної радіації, яка надходить до рослин, відіграють листкові пластинки.…”
unclassified